Adolescent stress: a multi-ethnic Asian perspective - Flett, Ross A.; Dharmanathan Selvanathan; Marsh, Nigel V. (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study was to examine gender and ethnic differences in adolescent stress in a non–Western context; multi-ethnic Malaysia. A Malay language version of the Adolescent Stress Questionnaire was administered to 300 adolescents aged from 13 to 17 years (Mean = 14.4 years). There were no statistically significant differences between genders or the three ethnic groups (Chinese, Indian, and Malay) across the 10 subscales. There was a significant gender x ethnicity interaction for the school performance subscale with Indian boys reporting significantly higher stress. Gender and ethnic differences were evident at the item level with boys reporting higher stress than girls on 12% of the items. For 27 (47%) of the items on the scale the most frequent response was not at all stressful (or irrelevant to me). Discussion highlights the importance of further research on adolescent stress in the Asian context and acknowledges that Western cultural understandings of stress are not necessarily or inevitably the same as that found in Asian cultures.